Effect of plasma transfusion on serum amyloid A concentration in healthy neonatal foals and foals with failure of transfer of passive immunity. (24th February 2023) - Palmisano, Megan; Javsicas, Laura; McNaughten, Justin; Gamsjäger, Lisa; Renaud, David L.; Gomez, Diego E.
Abstract: Background: Anecdotal evidence suggests plasma transfusions increase serum amyloid A (SAA) concentrations in healthy neonatal foals making this marker of inflammation inappropriate for therapeutic decision making in such animals. Hypothesis/Objectives: Administration of hyperimmune fresh frozen plasma (FFP) increases SAA concentration in healthy foals and in foals with failure of transfer of passive immunity (FTPI). Animals: Eighty‐six healthy foals. Methods: Prospective cohort study. Foals <24 hours of age receiving plasma transfusion for treatment of FTPI (serum immunoglobulin G [IgG] concentrations <8 g/L; n = 17) or as a preventative measure for Rhodococcus equi infection (IgG >8 g/L; n = 33) were enrolled. A healthy nontransfused group of foals (IgG >8 g/L; n = 21) also was included. Serum amyloid A concentration was determined before (t0h) and after (t24h) administration of FFP. Changes in blood SAA concentration were assessed using linear regression models. Results: No statistical differences were found in SAA concentration at t0h or t24h among the 3 groups ( P  > .05, for all comparisons). The variation in SAA concentration before (t0h) and after (t24h) plasma transfusion showed that administration of FFP was not associated with the changes in SAA concentration ( P  > .05). An association between SAA concentration at t0h and at 24 hours ( P  < .05) was identified, where foals with higher SAA concentration at t0h also had higher SAA concentration at t24h. Conclusions and Clinical Importance: Administration of FFP to newborn foals was not associated with changes in SAA concentration.